The e-krona and the macroeconomy - Hanna Armelius; Paola Boel; Carl Andreas Claussen; Marianne Nessén (Sveriges Riksbank Economic Review, 2018)
In this article, we discuss potential implications of an e-krona for the conduct of monetary policy and for macroeconomic developments in general. We argue that a universally accessible, non-interest-bearing e-krona supplied according to demand would establish a zero interest-rate floor for the policy rate and possibly all other interest rates in the economy. The effect of quantitative easing can thereby also be reduced. Furthermore, it is unlikely that the monetary policy transmission mechanism would be strengthened by an e-krona. We also note that international financial flows may increase and induce more exchange rate volatility. Finally, an e-krona could have long-run level effects on economic activity. The effects would be positive if an e-krona improves the efficiency and the resilience of the payment system and negative if an e-krona impinges on the supply of credit and financial stability.
Keywords: E42; E43; E44; E52; E58; 330; CBDC; monetary policy; macro economy